2007
DOI: 10.1200/jco.2006.07.4062
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Complications Associated With Sentinel Lymph Node Dissection (SLND) Plus Axillary Lymph Node Dissection Compared With SLND Alone in the American College of Surgeons Oncology Group Trial Z0011

Abstract: In trial Z0011, the use of SLND + ALND resulted in more wound infections, axillary seromas, and paresthesias than SLND alone. Lymphedema was more common after SLND + ALND but was significantly different only by subjective report. The use of SLND alone resulted in fewer complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
446
5
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 774 publications
(466 citation statements)
references
References 30 publications
14
446
5
1
Order By: Relevance
“…56 Over the past decade, less invasive surgical techniques such as sentinel lymph node biopsy and breast-conserving surgery have reduced the overall incidence of lymphedema; however, conservative estimates for incidence after sentinel lymph node biopsy are still in the range of 7%. 57,58 For high-risk patients treated with adjuvant radiation to a dissected axilla, the risk of subsequent lymphedema is greatly increased, with reported rates close to 45%. 7 Other breast cancer-related lymphedema risk factors for which data were not available in this systematic review of nonbreast cancer lymphedema studies include patient age, obesity, tumor factors, lymph node status, the presence of postoperative seroma or infection, and the presence of venous obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…56 Over the past decade, less invasive surgical techniques such as sentinel lymph node biopsy and breast-conserving surgery have reduced the overall incidence of lymphedema; however, conservative estimates for incidence after sentinel lymph node biopsy are still in the range of 7%. 57,58 For high-risk patients treated with adjuvant radiation to a dissected axilla, the risk of subsequent lymphedema is greatly increased, with reported rates close to 45%. 7 Other breast cancer-related lymphedema risk factors for which data were not available in this systematic review of nonbreast cancer lymphedema studies include patient age, obesity, tumor factors, lymph node status, the presence of postoperative seroma or infection, and the presence of venous obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Seven trials were thus eligible, as shown in Table 1 [3,4,[7][8][9][10][11]. A total of 9,608 patients were randomly assigned to treatment (658 in the SNB only arm, 5,084 in the ALND only arm and 4,406 who had SNB and then went onto have ALND), and data was available for analysis from 8,853 of them (636, 4,389 and 3,828 in the three arms, respectively).…”
Section: Eligible Studiesmentioning
confidence: 99%
“…There was little variability among studies in the menopausal status, eligible stages of breast cancer and tumour size of participants. All seven trials enroled patients between 1998 and 2005, and six of the seven studies were multicentre trials [4,[7][8][9][10][11].…”
Section: Eligible Studiesmentioning
confidence: 99%
See 2 more Smart Citations